Three essays on the effects of oil prices on imports and exports to China - Liu, Jiazhen (Kansas State University, 2024)
This dissertation consists of three essays: In the first study, I investigate the macroeconomic response of Asian crude oil importers to oil supply news shocks based on OPEC public announcements using a Structural VAR framework. I look into the macro aspects of the seven largest crude oil importers in Asia through exchange rate channels. My empirical results on the economic aspects indicate that Asian oil importers’ economies receive effect from oil supply news shocks, especially aggregated exports and aggregated imports. My analysis suggests that the effective exchange rate can be an additional channel through which oil news shocks affect the Asian economies indirectly. In terms of the second study, I investigate the export prices for primary agricultural commodities in responses to oil supply news shocks based on the OPEC public announcements. The research is carried out using a Structural VAR instrumented variable framework. I look into the primary agricultural commodities sold from ASEAN members to China, including rubber, palm oil and rice. My empirical results indicate that export prices for primary agricultural commodities in ASEAN receive in but short-run effects from oil supply news shocks. My findings also suggest that the shipping costs between ASEAN and China may be a key channel for the information transmitted from the oil supply news shocks to the ASEAN agricultural commodities prices. The third essay looks into the Chinese non-ferrous metal imports in response to the oil supply news shocks based on the OPEC public announcements as well as the Chinese trade policy uncertainty. The research on oil supply news is carried out using a Structural VAR instrumented variable framework while the trade policy uncertainty is investigated with TVPVAR model. In this paper, I look into the primary non-ferrous metals imported by China, including copper, nickel, aluminum, lead, zinc and tin. My empirical results indicate that the values and spot prices of Chinese non-ferrous metal imports receive little effects from the oil supply news shocks due to contract settlement method. My findings also suggest that an increasing of the Chinese trade policy uncertainty leads to diverse responses of the non-ferrous metal import values but negative responses for the non-ferrous metal import prices.
Keywords: Oil price shocks; Trade; China